Pengembangan Media Pembelajaran Game PowerPoint Interaktif Materi “Operasi Penjumlahan dan Pengurangan” pada Mata Pelajaran Matematika untuk Siswa Kelas 2 Sekolah Dasar - Aisyah, Adinda Siti; Amimufida, Salma Salsabilla; Ningsih, Intan Anzar Wahyu; Mahmudah, Alya Luthfia Choirina; Oktavia, Zeti Eka Ramaniza; Istiq’faroh, Nurul; Zahroh, Ulfi Amanatuz (Journal of Contemporary Issues in Primary Education, 2025)
In the learning process in the classroom, a pleasant learning atmosphere must be created so that students remain motivated to enthusiastically learn, one of which is by using Interactive PowerPoint Game learning media. This learning media can make students more active, learning becomes interactive and fun, and can educate students by playing while learning. The purpose of developing learning media is to determine the feasibility and practicality of Interactive PowerPoint Games in learning mathematics in the classroom. The method used in this research is the Analyze, Design, Development, Implementation and Evaluation (ADDIE) model. Data collection techniques in this study used validation questionnaires and student response interviews. The results showed that validators and students gave positive responses to the Interactive PowerPoint Game learning media. It can be seen in the validation assessment of Interactive PowerPoint Games by several experts, namely material experts with an average score of 96.94% with very good criteria, media experts with an average score of 92.55% with very good criteria, and design experts with an average score of 87.44% with very good criteria. While the results of student response interviews as a whole gave positive responses. Based on the results of the study, it can be concluded that the learning media for Interactive PowerPoint Games is declared feasible and practical to use to meet the needs of innovative learning media and increase student motivation in learning.